Utilization of public and private health services by the population of Belo Horizonte - Carlos Henrique Campos Castanheira; Adriano Marçal Pimenta; Francisco Carlos Félix Lana; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To analyze the differences in health services utilization by users of Brazilian Unified Health System (SUS) and beneficiaries of Supplemental Health (SH). METHODS: A total of 288 adult subjects, residing in Belo Horizonte, who participated in the VIGITEL telephone survey in 2009, composed the sample, whose variables were analyzed according to the classification as users of SUS or beneficiaries of SH. Prevalence Ratios (PR), adjusted for sex, age and schooling, were calculated to evaluate differences between groups. RESULTS: Need and demand for health services were similar between groups, and users of SUS were less successful in obtaining service (PR = 0.78; p = 0.027). Most participants in both groups evaluated the health care received as very good/good without significant differences (72.1% for SUS, 84.0% for SH; p > 0.05). CONCLUSION: Although there are differences in the utilization of health services in Belo Horizonte, the service obtained is well rated by both users of SUS and health plans.